AKUNTABILITAS, TRANSPARANSI DAN PERAN PERANGKAT DESA DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA JENALAS KECAMATAN GEMOLONG KABUPATEN SRAGEN - Kusumaningrum, Putri Dewi; Suharno, Suharno; Widarno, Bambang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study aims to find out how the application of accountability, transparency and the role of village officials in the management of the Village Development Budget (APBDes) in Jenalas Village. This accountability and transparency in general in the government of Jenalas Village, Gemolong District, Sragen Regency has gone well, although there are still some weaknesses that must be addressed. according to the results of the analysis based on the stages of Village Fund management, namely at the stage of implementation, the implementation of rural infrastructure development activities, namely the construction of the cast road has been running as expected because the implementers of this development activity can be managed directly by the TeamImplementation of Activities formed by the Village Government.The sample in this study used 81 respondents from members of the Jenalas village community institution that were taken using the Purposive Sampling method. The results of the study identified that accountability, transparency and the role of village officials had a significant positive effect on the management of village income and expenditure budgets in Jenalas Village